The Mex67p-mediated nuclear mRNA export pathway is conserved from yeast to human. - Katahira, J (1999)
Human TAP is an orthologue of the yeast mRNA export factor Mex67p. In mammalian cells, TAP has a preferential intranuclear localization, but can also be detected at the nuclear pores and shuttles between the nucleus and the cytoplasm. TAP directly associates with mRNA in vivo, as it can be UV-crosslinked to poly(A)+ RNA in HeLa cells. Both the FG-repeat domain of nucleoporin CAN/Nup214 and a novel human 15 kDa protein (p15) with homology to NTF2 (a nuclear transport factor which associates with RanGDP), directly bind to TAP. When green fluorescent protein (GFP)-tagged TAP and p15 are expressed in yeast, they localize to the nuclear pores. Strikingly, co-expression of human TAP and p15 restores growth of the otherwise lethal mex67::HIS3/mtr2::HIS3 double knockout strain. Thus, the human TAP-p15 complex can functionally replace the Mex67p-Mtr2p complex in yeast and thus performs a conserved role in nuclear mRNA export.